The impact of temperature and precipitation on blacklegged tick activity and Lyme disease incidence in endemic and emerging regions. Issue 1 (December 2016) - Burtis, James; Sullivan, Patrick; Levi, Taal; Oggenfuss, Kelly; Fahey, Timothy; Ostfeld, Richard
Abstract Background The incidence of Lyme disease shows high degrees of inter-annual variation in the northeastern United States, but the factors driving this variation are not well understood. Complicating matters, it is also possible that these driving factors may vary in regions with differing histories of Lyme disease endemism. We evaluated the effect of the number of hot (T > 25 °C), dry (precipitation = 0) days during the questing periods of the two immatureIxodes scapularis life stages (larval and nymphal) on inter-annual variation in Lyme disease incidence between 2000 and 2011 in long-term endemicversus recently endemic areas. We also evaluated the effect of summer weather on tick questing activity and the number of ticks found on small mammals between 1994 and 2012 on six sites in Millbrook, NY. Results The number of hot, dry days during the larval period of the previous year did not affect the human incidence of Lyme disease or the density of questing nymphs the following season. However, dry summer weather during the nymphal questing period had a significant negative effect on the incidence of Lyme disease in the long-term endemic areas, and on the density of questing nymphs. Summer weather conditions had a more pronounced effect on actively questingI. scapularis collectedvia dragging than on the number of ticks found feeding on small mammals. In recently endemic areas Lyme disease incidence increased significantly over time, but no trend was detected between disease incidence and dry summer weather. Conclusions Recently endemic regions showed an increase in Lyme disease incidence over time, while incidence in long-term endemic regions appears to have stabilized. Only within the stabilized areas were we able to detect reduced Lyme disease incidence in years with hot, dry summer weather. These patterns were reflected in our field data, which showed that questing activity of nymphalI. scapularis was reduced by hot, dry summer weather.